The Effect of Social Skill Training Therapy on Communication Skills in Socially Isolated Patients: A Literature Review - Ira Ocktavia Siagian (Indonesian Journal of Global Health Research, 2025)
Social isolation is a condition in which an individual is unable or has difficulty interacting with people around them. Individuals in this condition may feel alienated, rejected, lonely, and struggle to form meaningful relationships with others. Social Skills Training (SST) is an intervention that utilizes behavior modification techniques through role-playing, practice, and feedback. The goal of SST is to improve an individual's ability to deal with social problems, especially in clients with interaction disorders such as social isolation and anxiety. This therapy helps develop important communication and social skills needed in everyday life. This study used a systematic literature review method by analyzing 13 relevant journal articles published between 2020 and 2025. The results showed that SST was effective in improving social interactions in patients with social isolation. This therapy helps patients develop communication skills, reduce psychological symptoms, and improve cognitive function and social behavior. SST functions as an appropriate nursing intervention to help patients solve problems and build better social relationships.